PVDF-PZT nanohybrid based nanogenerator for energy harvesting applications - Shivaji H. Wankhade; Shivam Tiwari; Anupama Gaur; Pralay Maiti (Energy Reports, 2020)
With the depletion of the conventional energy sources, measures are being taken to create an alternate energy sources for the future. Energy harvesting from different sources are one of the better steps taken in this direction. Mechanical energy harvesting from the waste mechanical source is gaining profound investigation. Here, a nanohybrid of poly(vinylidene fluoride) and lead zirconia titanate (PZT) is prepared through solution route for energy harvesting applications. PZT is synthesized using solid state route and its concentration was varied in the nanohybrid to get the best properties from the hybrid. Structural and morphological aspects of the nanohybrid have been explored for their suitable application. Device has been fabricated using the nanohybrid to convert the waste mechanical energy from various human motions to the useful electrical energy. The device is able to generate a maximum output voltage of 55 V and a power density of 36 μWcm-2. The device is able to produce voltage output from different human motions such as finger tapping, feet tapping and bending. The mechanism of charge conversion is also discussed which explains the generation of such a high electrical output from waste mechanical source.
Keywords: 330; Energy harvesting; Nanohybrid; Piezoelectricity; PVDF; PZT